Application of Behavioristic Learning Theory in Thematic Learning - Istiqomariyah, Istiqomariyah; Sutomo, Moh.; Fatmawati, Erma (EDUTEC : Journal of Education And Technology, 2023)
The aim of researching the application of behavioristic learning theory in thematic learning is to explore how the principles of behaviorism can be used to enhance the effectiveness of thematic learning. This research aims to examine the various ways in which behavioristic learning theory can be applied in the classroom setting, and to identify the benefits and limitations of using behaviorism in thematic learning. The approach used in this research is a qualitative approach. The location chosen by the researcher is MI Miftahul Ulum Sumberwuluh Candipuro Subdistrict, Lumajang Regency. This research uses qualitative descriptive data analysis with an interactive model according to the theory of Miles, Hubermen and Saldana. The result showed the teachers often provide stimulus to students in the learning process. Teachers also often ask questions to students as a reinforcement of the material studied, so teachers often reinforce the material presented. Assessment carried out by class II teachers in thematic learning class II at Madrasah Ibtidaiyah Miftahul Ulum Theme 4 Sub Theme 4 Learning to 2 in the form of daily assessments which include several aspects, namely attitude, knowledge and skills assessment.